2020
DOI: 10.1155/2020/4065978
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Therapeutic Effects of Tension Band with Cannulated Screw and Tension Band with Kirschner Wire on Patella Fracture

Abstract: Background. Patella fracture accounts for 1% of bone injury, of which anatomical reduction is of great significance to the recovery. Tension band with cannulated screw and Kirschner wire is commonly used methods for the treatment of displaced patella fracture. However, there is still some controversy on the clinical efficacy of the two treatment methods. Objective. This study aimed at comparing the therapeutic effects of the cannulated screw and Kirschner wire tension bands on patella fracture and at providing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…There were no statistically significant differences between the two groups, including age, side, gender, fracture classification, mechanism, fracture displacement, and operative time to injury.The average age of the 52 patients was 51.7 years old (range, 22-76 years old).In our study 5 patients (16.7%) had loss of knee motion, four of them were treated by Kwires, 5 patients (16.7%) had loss of reduction or implant failure, four of them were treated by K-wires, 6 patients (20%) had delayed or non-union, five of them were treated by Kwires, 10 patients (33.3%) had pain during movement, seven of them were treated by Kwires. By comparison between types of fixation among post-operative complication (loss of knee motion, loss of reduction, delayed or non-union and pain during movement) there was no statistically significant difference between (loss of knee motion, loss of reduction, delayed or nonunion and pain during movement) among types of fixation, which is in agreement with the study of Liu et al[10] which reported there was no significant difference in the incidence of knee joint movement limitation, traumatic arthritis, bursitis, displaced internal fixation, reduction loss, and delayed fracture healing between the two groups, but the total incidence of complications in the TBWCS group was lower than that in the TBWKW group.…”
supporting
confidence: 91%
“…There were no statistically significant differences between the two groups, including age, side, gender, fracture classification, mechanism, fracture displacement, and operative time to injury.The average age of the 52 patients was 51.7 years old (range, 22-76 years old).In our study 5 patients (16.7%) had loss of knee motion, four of them were treated by Kwires, 5 patients (16.7%) had loss of reduction or implant failure, four of them were treated by K-wires, 6 patients (20%) had delayed or non-union, five of them were treated by Kwires, 10 patients (33.3%) had pain during movement, seven of them were treated by Kwires. By comparison between types of fixation among post-operative complication (loss of knee motion, loss of reduction, delayed or non-union and pain during movement) there was no statistically significant difference between (loss of knee motion, loss of reduction, delayed or nonunion and pain during movement) among types of fixation, which is in agreement with the study of Liu et al[10] which reported there was no significant difference in the incidence of knee joint movement limitation, traumatic arthritis, bursitis, displaced internal fixation, reduction loss, and delayed fracture healing between the two groups, but the total incidence of complications in the TBWCS group was lower than that in the TBWKW group.…”
supporting
confidence: 91%
“…They concluded that TBCS had better functional scores, quality of life, post-operative pain, and lower complication rate than TBKW. However, operative time was not significantly different (23) .…”
Section: Discussionmentioning
confidence: 79%
“…The shortest period (mean 1.72 months)was related to the TBCS group in the Hancerli study (22) . the longest period for union (mean3.3 ±0.7 months) was related to the TBKW group in the Liu study (figure 3) (23) Complications and Hardware Failure; Non-favorable outcomes were reported in all studies. The risk of complications with TBKW was statistically higher than that with TBCS (OR = 0.26, 95% CI ) (p=0.004) figure 5.…”
Section: Post-operative Outcomes Operative Timementioning
confidence: 89%
“…With the extensive use of tension banding techniques and the continuous development of innovative fracture xation techniques, many studies have been conducted to improve the tension band technique. Some studies 12,24 have used two parallel Kirschner wires or hollow screws through the fracture plane in combination with a wire tension band to x patellar fractures. However, this can only be used for simple patellar fractures.…”
Section: Discussionmentioning
confidence: 99%